Os desafios da internacionalização da indústria do varejo brasileiro de supermercados: o crescimento do Condor Super Center analisado em um estudo de caso para ensino - Salceda, José Alberto (2015)
This work aims to offer a case study about a Brazilian food retailing company. The growth strategy is the central dilemma. Internationalize or not? At the moment, there's no one Brazilian company in this specific industry internationalized by the 'ownership strategy' with stores abroad. An historical view of the business and his founder is presented. Aspects of the sector in Brazil are showed too. The case puts in evidence characteristics of the organization and its president. This work presents more than solely a teaching case study. Theoretical approaches based in concepts from entrepreneurship, entrepreneurial orientation, international entrepreneurship and resource-based view are presented like alternative perspectives for the teacher. An introductory contextualization is made about the importance of the retailing internationalization in relation to network society. A comparison between case study for research and a teaching case is offered in the chapter about methodology. Disciplines like management strategy, entrepreneurship, internationalization, organizational theories, marketing and economics are suggested for the use of the case.